Delphi Process Recommendations for Pediatric Disaster Medicine Training Curriculum Key Competencies - Grodman, Schyler; Hard, Alexander; Hertelendy, Attila; Woodward, Christina; Voskanyan, Amalia; Issa, Fadi; Weiner, Debra; Ciottone, Greg (Prehospital and disaster medicine, 2023)
Introduction:Children differ from adults, developmentally, physiologically, and psychologically. Additionally, children lack legal agency, and thus rely on adults to gain access to the healthcare system and other resources. Though children are often the face of disaster relief, the desparate needs of children can fall through the cracks during disaster response. Many training programs for disaster responders do not give pediatric concerns and issues the appropriate attention they deserve. Pediatric disaster medicine is often minimally addressed in emergency medicine residencies and prehospital provider training. Furthermore, pediatric disaster supplies and protocols are often lacking and insufficient to meet the needs of children during and after disasters.Method:This is a modified Delphi study. An initial set of pediatric disaster medicine competencies from a systematic review of PubMed, EMBase and the gray literature will be presented to an initial group of Subject Matter Experts (SMEs) comment, additions, and edits. This modified set of competencies will then be distributed to a large group of providers with experience in the field. Through a series of surveys, each competency in the curriculum will be rated. Those competencies which achieve a high overall rating will be reported.Results:Data collection and analysis expected to be completed by April 2023.Conclusion:This modified Delphi study will establish and prioritize a set of core competencies for pediatric disaster response based on expert recommendations. The use of such gold standard core competencies to develop discipline-role-specific pediatric disaster training can increase pediatric disaster workforce capacity and competency critically needed to improve pediatric disaster response.